(3LfI GdEjeGf GdhGbjI hLfI GdEjeGf GdHGbjIs - (3GdcaYej, EHQGgje Hf Ydj Hf GdMSf, J(B905(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdOYGA SdeG hHYO agPG cJGH eMJh Ydi YhP hOYhGJ hJSGHjM hRjGQGJhSejJ eG LeYJg HGdLfI GdhGbjI hGdLfI GdHGbjIs
(3BNQgG (B:s
(3cJGH GdLhGgQ cJGH GdYOI cJGH GdJJeI Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 53s
(3eYLe GdeDdajf(B: 3 / 46s
(3EjVGM Gdecfhf(B: 1 / 369s
(3CYjGf GdTjYI(B: 5 / 336s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs